Alteration of the E-Cadherin/β-Catenin Complex Is an Independent Poor Prognostic Factor in Lung Adenocarcinoma - Kim, Hyojin (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2013)
BACKGROUND: Epithelial-mesenchymal transition (EMT) is an important step in the invasion and progression of cancer and in the development of chemoresistance by cancer cells. METHODS: To address the clinical significance of the EMT pathway in lung adenocarcinoma and the association of the pathway with histological subtype, we examined 193 surgically resected lung adenocarcinoma samples for the expression of representative EMT-related proteins (E-cadherin, β-catenin, and vimentin) by immunohistochemistry. Histological subtypes were classified according to the 2011 International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society classification. The results for EMT-related protein expression were analyzed for correlation with clinicopathological features and with survival. RESULTS: The loss of E-cadherin expression and aberrant β-catenin expression were significantly associated with larger tumor size, pleural invasion, lymphatic/vascular invasion, and advanced pathological stage (p<0.05). The alteration of the E-cadherin/β-catenin complex was least frequently observed in the lepidic-predominant group, but these associations were not statistically significant. In the multivariate analysis, altered E-cadherin/β-catenin complex expression was found to be an independent poor prognostic factor (p=0.017; hazard ratio, 1.926; 95% confidence interval, 1.119 to 3.314). CONCLUSIONS: The alteration of the expression of the E-cadherin/β-catenin complex was associated with aggressive tumor behavior in lung adenocarcinoma.